Everyday Political Objects From the Middle Ages to the Contemporary World (Taylor & Francis, 2021)
Ages, Christopher, Contemporary, Everyday, Fletcher, Middle, Objects, Political, World
English
Keywords: European history; General and world history; History; Microbiology (non-medical); Ages, Christopher, Contemporary, Everyday, Fletcher, Middle, Objects, Political, World